TRANSLATION TECHNIQUES AND QUALITY ASSESSMENT ON CNN NEWS - Nabilla, Jauzia Yusi Hilmi; Fatimah, Rezki (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Advancements in technology enable a swifter translation process, enhancing the circulation of information on a global scale. Nevertheless, the translation process requires supervision to maintain the quality of the news, to ensure the essence of the information is accurately conveyed in the translated output. There are various translation techniques, and typically, each agency has its own standards and regulations governing the techniques and structures. This study aims to analyze the translation techniques in translating CNN news using Molina and Albir (2004) framework and assess the translation quality using Nababan (2015) parameters. It is found that the first news translation has high accuracy but with low acceptability and readability, indicating that the translation results tend to be faithful but sacrifice the other two aspects. The second news translation tends to prioritize the presentation of readings that are easier to understand and accept by readers, but has an impact on low accuracy. The third news translation tends to be able to balance the three aspects with a difference in the average score of accuracy (2.67), which is closely aligned with the scores for acceptability and readability. Based on the final calculation with weighted scores, the results obtained show that overall, the CNN Indonesia translator succeeded in translating CNN International news well and obtained a final average score of 2.70, which is very close to the maximum score of 3.0.